Commentary: Oral rehydration solution - Fontaine, O. (1998)
Although it had been shown as early as 1968 that oral rehydration therapy was as effective as intravenous rehydration therapy in the treatment of dehydration due to diarrhoea, use of oral rehydration therapy was limited to rural health centres. In large urban hospitals oral rehydration therapy was held to be inferior to intravenous therapy and tended to be used only when the latter was not available. The results reported in the article by Samadi et al. in 1983 were extremely important in helping to change these practices and today paediatricians in large referral hospitals all over the world have been convinced of the practical advantage provided by oral rehydration solution, saving money, space and time.